Innovation practices for survival of small and medium enterprises (SMEs) in the COVID-19 times: The role of external support - Nawal Abdalla Adam; Ghadah Alarifi (Journal of Innovation and Entrepreneurship, 2021)
Global epidemic crises, such as the coronavirus (COVID-19), usually expose small and medium enterprises (SMEs) to various kinds of challenges and may put their lives at risk. This study aims to develop a theoretical model to provide insights about the association between innovation practices and the SMEs' performance and survival while underlining the auxiliary role of external support in such a relationship. Online questionnaire has been used to collect the data from 259 randomly selected SME managers in Saudi Arabia, and the data was analyzed using the SmartPLS3 software. The structural equation modeling results showed that the innovation practices adopted by SMEs to face the repercussions of COVID-19 had a positive impact on the performance and likelihood of business survival. PLS-SEM bootstrap results indicated that external support aids strengthen the positive impact of SMEs' innovation practices on business survival rather than its performance. The study has several significant practical implications for SME managers, governments, and policy makers that have been stated.
Keywords: 650; Coronavirus (COVID-19) crisis; External support; Innovative practices; Small- and medium-sized enterprises (SMEs); SME performance; SME survival